Morphology Transformation of Foldamer Assemblies Triggered by Single Oxygen Atom on Critical Residue Switch. Issue 36 (26th July 2021) - Oh, Byung‐Chang; Yoon, Eunyoung; Gong, Jintaek; Kim, Jaewook; Driver, Russell W.; Kim, Yongjun; Kim, Woo Youn; Lee, Hee‐Seung
Abstract: The synthesis of morphologically well‐defined peptidic materials via self‐assembly is challenging but demanding for biocompatible functional materials. Moreover, switching morphology from a given shape to other predictable forms by molecular modification of the identical building block is an even more complicated subject because the self‐assembly of flexible peptides is prone to diverge upon subtle structural change. To accomplish controllable morphology transformation, systematic self‐assembly studies are performed using congener short β‐peptide foldamers to find a minimal structural change that alters the self‐assembled morphology. Introduction of oxygen‐containing β‐amino acid (ATFC) for subtle electronic perturbation on hydrophobic foldamer induces a previously inaccessible solid‐state conformational split to generate the most susceptible modification site for morphology transformation of the foldamer assemblies. The site‐dependent morphological switching power of ATFC is further demonstrated by dual substitution experiments and proven by crystallographic analyses. Stepwise morphology transformation is shown by modifying an identical foldamer scaffold. This study will guide in designing peptidic molecules from scratch to create complex and biofunctional assemblies with nonspherical shapes. Abstract : This study demonstrates a stepwise and controllable morphology transformation from molar‐tooth shape to gel via rectangular and truncated tilted prism shapes, designed by subtle electronic perturbation on the structurally well‐defined β‐peptide foldamer assemblies. This strategy provides powerful tools for developing morphology‐sensitive biological sensors and drug delivery vehicles.